2017
DOI: 10.1016/j.bandl.2016.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Visual statistical learning is related to natural language ability in adults: An ERP study

Abstract: Statistical learning (SL) is believed to enable language acquisition by allowing individuals to learn regularities within linguistic input. However, neural evidence supporting a direct relationship between SL and language ability is scarce. We investigated whether there are associations between event-related potential (ERP) correlates of SL and language abilities while controlling for the general level of selective attention. Seventeen adults completed tests of visual SL, receptive vocabulary, grammatical abil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 90 publications
(110 reference statements)
7
39
0
Order By: Relevance
“…Specifically, SL is suggested to provide a potentially powerful mechanism with which children can acquire language from input without strong assumptions about innateness (although see [16]). More recently, the field has attempted to quantify IDs in SL, and has linked these to language proficiency in children and adults [105][106][107][108][109][110][111][112]132]. This work has shown some promise, with mostly medium-positive associations between SL and language typically reported [133].…”
Section: Box 1 Ids In Statistical Learning and Their Relationship Tomentioning
confidence: 86%
See 1 more Smart Citation
“…Specifically, SL is suggested to provide a potentially powerful mechanism with which children can acquire language from input without strong assumptions about innateness (although see [16]). More recently, the field has attempted to quantify IDs in SL, and has linked these to language proficiency in children and adults [105][106][107][108][109][110][111][112]132]. This work has shown some promise, with mostly medium-positive associations between SL and language typically reported [133].…”
Section: Box 1 Ids In Statistical Learning and Their Relationship Tomentioning
confidence: 86%
“…IDs in SL have been linked to language proficiency across the lifespan, a relationship that has been attested across multiple domains of language, including vocabulary [105], grammatical [106], and literacy development in children [107]; and second language-learning adults [108]. The link is also attested in adults, and appears most strongly in tasks involving predictability; for instance, in predicting likely continuations of sentences in context [109] or in grammatical sequencing [110][111][112]. Similar effects have been observed in adult readers' use of orthographic cues for lexical access during reading [132].…”
Section: Interestingly Wm and Ef Are Interrelated (See Outstanding Qmentioning
confidence: 99%
“…As an additional control, the Stanford Sleepiness Scale (SSS) was administered at the beginning and end of the experiment to measure self-perceived sleepiness. A visual statistical learning task (for a detailed description, see Siegelman, Bogaerts, & Frost, 2016) was also administered, as statistical learning ability has been shown to predict individual differences in language learning ability (Daltrozzo et al, 2017).…”
Section: Screening and Control Measuresmentioning
confidence: 99%
“…As an exploratory analysis, we examined the relationship between statistical learning ability, task-evoked beta power and accuracy on the judgement tasks. This analysis was conducted to test the idea that statistical learning ability is a domain-general mechanism underlying language learning (Daltrozzo et al, 2017;Siegelman et al, 2016), and that language-related predictions during sentence processing are reflected in beta activity . In accord with prior literature, a beta regression indicated that statistical learning ability positively predicted proportion of correct responses (χ2(1) = 12.38, β = .01, pseudo R 2 = .29, p < .001).…”
Section: Statistical Learning Ability Modulates Task-evoked Beta Powermentioning
confidence: 99%
“…ERPs were also shown to differentiate between visual stimuli that carry high vs. low predictability for a subsequent target. Highly reliable predictors were shown to elicit either a larger centro-parietal late positivity (Daltrozzo et al, 2017) or a larger P300 component (Jost et al, 2015). More recently the predictability of visual stimuli was shown to modulate the low-frequency activity associated with stimulus presentation: in comparison to predictable second items of a learned pair, unexpected shapes elicited stronger activity in the alpha (7 -14 Hz) range (Zhou et al, 2019).…”
Section: Introductionmentioning
confidence: 99%